To evaluate the efficacy of topical propolis in the management of symptomatic oral lichen planus: A randomized controlled trial - Athira Joshy; Nagabhushana Doggalli; Karthikeya Patil; P K Kulkarni (Wolters Kluwer Medknow Publications, 2018)
Introduction: Lichen planus (LP) is a chronic inflammatory, autoimmune, mucocutaneous disease of unknown etiology. The first line of treatment for oral LP (OLP) has been corticosteroids, but because of their adverse effects, alternative therapeutic approaches are being carried out, of which the recent natural alternative is propolis. Aim: This study aims to evaluate the efficacy of topical propolis in the management of OLP. Materials and Methods: The research group consisted of 27 patients diagnosed with symptomatic OLP, among which 15 patients were in the control group and the rest 12 were in the study group. The patients in the control group received triamcinolone acetonide 0.1% (topical application) while the patients in the study group received propolis gel. Both the groups were evaluated for pain and erythema at baseline (1st visit), first follow-up (7th day), and second follow-up (14th day) using numerical rating scale and modified oral mucositis index. Results: The patients in both the study and control groups showed a statistically significant reduction (P = 0.000 for the study group and P = 0.000 for the control group) in pain and erythema scores from baseline to second follow-up visit. However, on comparison of the reduction in pain and erythema scores between the two groups, the difference was found to be statistically insignificant (P = 0.255). Statistical Analysis Used: Chi-square and Cramer's V test were used. Conclusion: The topical propolis was found to be of comparative effectiveness with respect to triamcinolone acetonide 0.1% in the management of OLP.